Opera omnia Desiderii Erasmi Roterodami Ordinis Noni Tomus Secundus - de Jonge, H.J (Huygens instituut/Brill, 1983)
The Apologia respondens ad ea quae Jacobus Lopis Stunica taxauerat in prima duntaxat Noui Testamenti aeditione is Erasmus' first apology against the Spaniard Stunica. Erasmus himself classed it under the eighth 'ordo' of his works, that is, the 'ordo' of his apologies; see Ep. I to Botzheim, 30 January 1523, p. 4 I, 1. 22, and cf. Ep. 2283 to Boece, 15 March 1530, 1. 189. Since the editors of BAS reserved the seventh 'ordo' ('tomus' in their terminology) for the Paraphrasis in Nouum Testamentum, in accordance with Erasmus' direction in the letter to Botzheim (Ep. I, p. 41, 1. 8), and the next 'ordo' for the translations from the Church Fathers, in accordance with the letter to Boece (Ep. 2283, 1. 155), the collected apologies eventually became the ninth 'ordo', not the eighth. In the present edition, the ~rst apology against Stunica is the second volume of the ninth 'ordo'. Four further apologies against Stunica and that against Carranza will form, or form part of, another volume. Interestingly enough, the first apology against Stunica is the first work of Erasmus whose final authentic redaction turns out not to be contained in an edition printed during Erasmus' lifetime, but in BAS. This remarkable fact as well as its consequences for the pres~nt edition will be discussed in detail in the Introduction, chapter VI. In addition to those who, at the request of the editorial board, took charge of the supervision of this volume and whose names are recorded on the verso of the title-page, M. de Jonge of Leiden has kindly read and criticized the typescript. The editorial board and the editor of the present volume thank all libraries who put books, photostats, microfilms and bibliographical material at theirdisposal. They would also like to thank Mrs Anna de Haas of the NorthHolland Publishing Company for the valuable assistance she has rendered in seeing this volume through the press.